Adsorption of carbazole from wastewater using cyclodextrin-rice husk biochar (cd-rhb) - Wee Chi, Chyin (2024)
Carbazole (CBZ) is an emerging contaminant with various ecotoxicological effects, making its removal from wastewater crucial. This study focuses on β-cyclodextrin rice husk biochar (CD-RHB) for CBZ adsorption. CD-RHB was synthesized through β-CD and rice husk biochar cross-linking using phosphoric acid. The objective is to investigate CD-RHB's adsorption capability for CBZ removal from contaminated wastewater. The study compares CD-RHB's performance with rice husk biochar (RHB) and activated-rice husk biochar (ARHB). Results demonstrate CD-RHB's superior efficiency over ARHB and RHB. The methodology employs CD-RHB for CBZ removal from synthetic wastewater, determining adsorption conditions (dosage, initial CBZ concentration, contact time). Using optimal parameters, CD-RHB achieved 17.45 mg CBZ/g and 87.25% removal efficiency. However, this rate falls short of meeting the CBZ threshold limit value (0.01 mg/L) for wastewater treatment. In conclusion, optimal conditions maximizing adsorption performance involve using 0.04 g of CD-RHB for treating wastewater with 40 mg/L CBZ over 210 minutes. This research provides insights into the sustainable use of CD-RHB for effective CBZ removal from contaminated wastewater.